West Nile Virus and High Death Rate in American Crows - Yaremych, Sarah A. (Centers for Disease Control and Prevention, 2004)
We document effects of West Nile virus (WNV) on American Crows. More than two thirds of our crows died of WNV infection, peaking when the proportion of infected mosquitoes at roosts was greatest. WNV antibody prevalence in crows was low. Local ecologic effects can be dramatic as WNV inhabits new areas.